Pengelompokan Kegiatan di Ruang Publik berdasarkan Waktu, Intensitas, dan Usia - Rafidah Azzar Dea; Annisa Safira Riska; Hanson Endra Kusuma (RUAS, 2021)
On a city scale, public spaces are often an effective place for urban people to carry out various activities and social interactions. In this space, people can carry out their various needs, both physical needs such as sports, gathering, work, and spiritual needs such as relaxation, getting out from everyday boredom, and so on. This study aims to determine how the grouping of activities that occur in a public space based on time, intensity of visits, and the age of visitors. This research applied an exploratory qualitative grounded theory approach. After the data was collected through an online questionnaire, the data was processed in three stages, namely open coding, axial coding, and selective coding. The results of the study revealed that there are four large groups of activities that are usually carried out in public spaces based on time, intensity, and age. The four groups are groups of health, hobby, relaxation, and lust activities.